Pemenuhan Unsur Kerugian Keuangan Negara Sebagai Dasar Pembuktian pada Proses Penetapan Tersangka dalam Perkara Tindak Pidana Korupsi (Studi Putusan Praperadilan Nomor 113/Pid.Pra/2024/Jkt.Sel) - Kuswandari , Dina Tri; Umara, Nanda Sahputra (Indonesian Journal Publisher, 2025)
The enforcement of criminal law on corruption in Indonesia faces a complex dilemma between efforts to eradicate corruption and the protection of human rights, particularly in the process of determining suspects in cases involving financial losses to the state. Constitutional Court Decision No. 25/PUU-XIV/2016 has clarified that financial loss to the state under Articles 2 and 3 of the Corruption Criminal Law must be actual loss, not potential loss. This study analyzes the fulfillment of the criminal elements of Articles 2 and 3 of Law No. 31 of 1999 as a requirement for suspect designation and evaluates its application in Pre-Trial Ruling No. 113/PID.PRA/2024/JKT.SEL. Using a normative legal research method with a legislative and case-based approach, the study analyzes relevant regulations, court decisions, and legal doctrines. The results of the study indicate that the element of financial loss to the state is an absolute requirement in the designation of corruption suspects through the application of the relevance theory. Investigators must have evidence from an investigative audit by the State Audit Agency (BPK/BPKP) showing actual loss before designating a suspect. The study concludes that the designation of a corruption suspect must be supported by measurable evidence of state financial loss from the competent authority. The preliminary hearing decision was legally flawed because it did not apply the evidentiary standards in accordance with criminal procedural law and the material elements of the corruption offense.